Bilirubin Links Heme Metabolism to Neuroprotection by Scavenging Superoxide. Issue 10 (17th October 2019) - Vasavda, Chirag; Kothari, Ruchita; Malla, Adarsha P.; Tokhunts, Robert; Lin, Anthony; Ji, Ming; Ricco, Cristina; Xu, Risheng; Saavedra, Harry G.; Sbodio, Juan I.; Snowman, Adele M.; Albacarys, Lauren; et al.
Summary: Bilirubin is one of the most frequently measured metabolites in medicine, yet its physiologic roles remain unclear. Bilirubin can act as an antioxidant in vitro, but whether its redox activity is physiologically relevant is unclear because many other antioxidants are far more abundant in vivo . Here, we report that depleting endogenous bilirubin renders mice hypersensitive to oxidative stress. We find that mice lacking bilirubin are particularly vulnerable to superoxide (O2 ⋅− ) over other tested reactive oxidants and electrophiles. Whereas major antioxidants such as glutathione and cysteine exhibit little to no reactivity toward O2 ⋅−, bilirubin readily scavenges O2 ⋅− . We find that bilirubin's redox activity is particularly important in the brain, where it prevents excitotoxicity and neuronal death by scavenging O2 ⋅− during NMDA neurotransmission. Bilirubin's unique redox activity toward O2 ⋅− may underlie a prominent physiologic role despite being significantly less abundant than other endogenous and exogenous antioxidants. Graphical Abstract: Highlights: Eliminating endogenous bilirubin renders cells vulnerable to oxidative stress Bilirubin exhibits distinct redox activity among endogenous small molecules Bilirubin scavenges O2 ⋅− Neural bilirubin prevents NMDA receptor excitotoxicity by scavenging O2 ⋅− Abstract : Bilirubin is routinely measured in clinical blood tests, yet its physiologic functions remain unclear. Here, Vasavda et al. report that bilirubin is a physiologic antioxidant with distinct chemical activity toward superoxide, a reactive oxygen anion. They find that bilirubin is neuroprotective, in part by regulating superoxide signaling during neurotransmission.